Solving the coupled thermal problems and the thermal load transfer between a fluid and a solid body - Volkov, K.N. (Numerical Methods and Programming (Vychislitel'nye Metody i Programmirovanie), 2007)
Some questions concerning the development and implementation of software designed for the numerical solution of coupled thermal analysis problems are considered. The thermal load transfer between computational modules, a formulation of boundary conditions on the fluid-solid interface, and the implementation of some additional capabilities to save computer time are discussed. The numerical results obtained for the temperature distribution in a free rotating disk and for the metal and fluid temperature fields inside a cavity bounded by stationary and rotational disks are compared with experimental data and with the theoretical dependencies.